Uporaba avtentičnih posnetkov pri pouku italijanščine za odrasle - Pegam, Polona (Vestnik za tuje jezike, 2015)
The article aims to outline the practical value of authentic recordings in teaching Italian to adults. Occasional use of such didactic recordings as extra material during the learning process represents an added value. Chosen recordings are adapted to a particular group and so is the content of the material. Such material presents an attractive way of practicing language skills by encouraging students to be more in contact with the actual language outside of the classroom. Learning Italian in the areas away from the Slovenian-Italian border is different because there is less everyday contact with the "living" language. By using authentic recordings the listening input is increased. When the use of authentic listening is also visually supported, the final intake and the memorising of the information are much easier.
Keywords: Italian; italijanščina; tuji jeziki; didactic method; didaktika; jezikovne spretnosti; avtentični posnetki; odrasli